Peran Muhammad Ibnu Sahnun dalam Membangun Sistem Manajemen Pendidikan Berbasis Nilai Islam - Murtopo, Ali (El-Idare, 2024)
Muhammad Ibnu Sahnun's thoughts on educational management offer highly relevant guidelines for curriculum management within the context of Islamic education. In his work, Ibnu Sahnun emphasizes the importance of a curriculum balanced between general knowledge and religious education, making religious education the moral foundation that underpins all learning. In the modern era, marked by technological advancements, globalization, and rapid social dynamics, the educational management principles proposed by Ibnu Sahnun remain significant. He emphasizes values such as honesty, justice, and responsibility as the foundation for managerial decisions in educational institutions. Additionally, Ibnu Sahnun highlights the importance of students' rights, stressing the need for a balance between their rights and responsibilities in the educational process. By adhering to these principles, educational administrators can create an environment that supports the holistic development of students, both academically and morally. In the context of modern management, Ibnu Sahnun's ideas provide a strong foundation for building an educational system that not only focuses on administrative aspects but also on character formation and the development of beneficial knowledge. Therefore, the educational management principles offered by Ibnu Sahnun remain relevant and can be applied to improve the quality of education in the contemporary era.